In-silico analysis of water and carbon relations under stress conditions. A multi-scale perspective centered on fruit - BALDAZZI, Valentina; PINET, Amélie; VERCAMBRE, Gilles; BENARD, Camille; BIAIS, Benoît; GENARD, Michel (Frontiers in Plant Science, 2013)
Fruit development, from its early stages, is the result of a complex network of interacting processes, at different scales. These include cell division, cell expansion but also nutrient transports from the plant and exchanges with the environment. In the presence of nutrients limitation, in particular, the plant reacts as whole, by modifying its architecture, metabolism and reproductive strategy, determining the resources available for fruits development, which in turn affects the overall source-sink balance of the system. Here we present an integrated model of tomato that explicitly accounts for early developmental changes (from cell division to harvest), and use it to investigate the impact of water deficit and carbon limitation on nutrient fluxes and fruit growth, in both dry and fresh mass. Variability in fruit response is analyzed at two different scales: among trusses, at the plant level and within the cells population, at the fruit scale. Results show that the effect of stress on individual cells strongly depends on their age, size and uptake capabilities and that the timing of stress application, together with the fruit position on the plant, is crucial to determine the final phenotypic outcome. Water deficit and carbon depletion impacted either source size, source activity or sink strength with contrasted effects on fruit growth. An important prediction of the model is the major role of symplasmic transport of carbon in early stage of fruit development, as a catalyst of cells and fruit growth.